Identification of calcium pyrophosphate deposition disease (CPPD) by ultrasound: reliability of the OMERACT definitions in an extended set of joints—an international multiobserver study by the OMERACT Calcium Pyrophosphate Deposition Disease Ultrasound Subtask Force. Issue 8 (13th March 2018) - Filippou, Georgios; Scirè, Carlo Alberto; Adinolfi, Antonella; Damjanov, Nemanja S; Carrara, Greta; Bruyn, George A W; Cazenave, Tomas; D'Agostino, Maria Antonietta; Delle Sedie, Andrea; Di Sabatino, Valentina; Diaz Cortes, Mario Enrique; Filippucci, Emilio; et al.
Abstract : Objectives: To assess the reliability of the OMERACT ultrasound (US) definitions for the identification of calcium pyrophosphate deposition disease (CPPD) at the metacarpal-phalangeal, triangular fibrocartilage of the wrist (TFC), acromioclavicular (AC) and hip joints. Methods: A web-based exercise and subsequent patient-based exercise were carried out. A panel of 30 OMERACT members, participated at the web-based exercise by evaluating twice a set of US images for the presence/absence of CPPD. Afterwards, 19 members of the panel met in Siena, Italy, for the patient-based exercise. During the exercise, all sonographers examined twice eight patients for the presence/absence of CPPD at the same joints. Intraoberserver and interobserver kappa values were calculated for both exercises. Results: The web-based exercise yielded high kappa values both in intraobserver and interobserver evaluation for all sites, while in the patient-based exercise, inter-reader agreement was acceptable for the TFC and the AC. TFC reached high interobserver and intraobserver k values in both exercises, ranging from 0.75 to 0.87 (good to excellent agreement). AC reached moderate kappa values, from 0.51 to 0.85 (moderate to excellent agreement) and can readily be used for US CPPD identification. Conclusions: Based on the results of our exercise, the OMERACT US definitions for the identification of CPPD demonstrated to be reliable when applied to the TFC and AC. Other sites reached good kappa values in the web-based exercise but failed to achieve good reproducibility at the patient-based exercise, meaning the scanning method must be further refined.